Pengaruh Lingkungan Belajar Terhadap Motivasi dan Kreativitas Siswa di SMP Negeri 20 Surabaya - Galih Rachmad Pratama; Siti Aminah; Amira Wahyu Utami; Shelma Devanatasha; Kaniati Amalia (CV Putra Publisher, 2025)
This study aims to see how motivation and learning environment affect students' motivation and creativity at SMPN 20 Surabaya. Motivation and learning environment have an important role in the learning process that can improve student learning outcomes. A comfortable and supportive environment can encourage creativity and increase students' enthusiasm for learning to achieve learning goals. This research uses a qualitative method with a descriptive approach to understand how a positive environment affects students' motivation and creativity. The results show that a comfortable environment and complete facilities, such as reading corners, libraries and laboratories, are very influential in developing students' creativity. In addition, the role of teachers is also very important to create a supportive and conducive learning atmosphere, appreciate the ideas put forward by students, and encourage them to be more creative and motivated to do more activities in the future. Therefore, schools need to create a supportive learning environment and provide opportunities for students to develop their talents and interests to the fullest.